Racing Performance and Sale Result in 145 Thoroughbreds after Arthroscopic Removal of Osteochondral Fragments from the Lateral Femoral Trochlear Ridge as a Yearling (2012–2015) - Kerbert, Maria P.; Freeland, Russell B.; Verhaar, Nicole; Baker, William T. (Veterinary and Comparative Orthopaedics and Traumatology, 2023)
Objectives The lateral trochlear ridge (LTR) of the femur is the most common predilection site for osteochondritis dissecans (OCD) in the equine stifle. The objective was to investigate the relationship between lesion size, racing performance, and sale result of Thoroughbreds with LTR OCD following arthroscopic removal as a yearling.Methods In this retrospective study, medical records of 145 Thoroughbreds from one equine hospital that underwent surgery for LTR OCD were reviewed; the length and depth of the lesions were measured on preoperative radiographs. Horses were allocated to group S if they were presented to a public yearling sale post-surgery, and horses in group NS were not. Each horse from group S was matched with two control horses from the same sale (group C). Influence of lesion size on racing performance and sale result was analyzed. Racing performance and sale results were compared between different categories of OCD lesion sizes and between the groups.Results Lesion length and depth did not affect racing performance and did not differ between group S and group NS. However, group S did perform significantly better than group NS. When comparing groups S and C, there were no significant differences in racing performance and sale result.Conclusion Thoroughbreds that had arthroscopic surgery for LTR OCD as a yearling and were presented on a public yearling sale performed comparable to Thoroughbreds that showed similar potential as a yearling. Sale result is not significantly affected in our study.
Keywords: osteochondritis dissecans; stifle; Thoroughbreds; racing performance; sale